Existing infrastructure & adaptability of new technology regarding risk and fraud management in the online delivery platforms: A study on foodpanda Bangladesh (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.